Flotation bank air addition and distribution for optimal performance - Smith,CD; Hadler,K; Cilliers,JJ (Minerals Engineering, 2010)
Recent studies have shown that varying the distribution of a set volume of air to a flotation bank significantly affects the performance of the bank. To date, however, the volume of air to be distributed has usually been arbitrarily set as that added with the ‘as found’ air rates, the typical operating air rates; not necessarily an optimum.Studies examining the effect of different total air additions, at a constant distribution, have shown the addition maximising air recovery typically yields the best performance. Air recovery is the fraction of the air added to a cell which overflows the lip of the cell as unburst bubbles and shows a peak with respect to cell aeration.In this work three experimental case studies are presented to examine of the role of aeration in flotation performance, with the aim of developing a generic technique to determine both the required total air addition and distribution of air to a bank of flotation cells.The first case study compares performance at three different total air additions. The air addition which gave the Peak Air Recovery (PAR) also gave the highest mineral recovery. Thus air recovery optimisation yields the optimum total air addition to a flotation bank. In the second case study the air recovery was optimised from each cell in a bank individually. The PAR air addition once more gave the highest mineral recovery from the bank. Therefore, air recovery optimisation determines the optimum total air addition to a bank and also provides a distribution for that air. The third case study compares a profile based on the PAR air rates with other distributions of the same total air. The results show the profile based on the PAR air rates gave a significantly higher cumulative mineral recovery than other distributions of the same volume of air, for the same cumulative grade.The results of the three case studies show air recovery optimisation of each cell in a bank is a robust and generic technique to simultaneously determin